Study of Transport System in Japan - Planning Commission (Planning Commission, Government of India, 1970)
The “Study of Transport System in Japan” by Sat Parkash examines the rapid transformation of Japan’s transport infrastructure in the post-World War II period and its critical role in supporting the country’s extraordinary economic growth. Between 1960-61 and 1968-69, Japan experienced dramatic increases in gross national product, foreign trade, and domestic cargo movement, accompanied by a structural shift from rail to road transport. The report highlights the operations of Japan National Railways, including the introduction of the Tokaido Shinkansen, which significantly enhanced speed, efficiency, and revenue generation despite broader financial challenges within the railway network. Parallel to railway modernization, Japan invested heavily in road development, expanding its highway network through public corporations and road bonds, thereby strengthening motor transport’s dominance in domestic freight. The study also underscores the importance of merchant shipping, containerization, and port development in facilitating international trade, alongside the rapid expansion of civil aviation for passenger and cargo services. A key feature of Japan’s system is the evolution of an integrated freight forwarding mechanism that coordinates multimodal transport efficiently from producer to consumer. Overall, the report presents Japan’s transport development as a model of strategic investment, technological innovation, and integrated planning, offering valuable lessons for developing nations seeking to align infrastructure growth with economic advancement.
Government of India Planning Commission
Keywords: Japan Transport System; Post-War Economic Growth; Japan National Railways; Tokaido Shinkansen; Road Transport Expansion; Highway Development Corporations; Merchant Shipping Growth; Containerization; Civil Aviation Development; Freight Forwarding System; Multimodal Transport Integration; Infrastructure Investment Strategy